Competitiveness of Non-Traditional Agricultural Products 2009-2013 (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
This study aims to determine the relative advantage offered by nontraditional agricultural products. The outline evaluates a five-year period, the implanted statistics in the study, sources constituted by descriptive statistics using the concept of commercial rates that are an integral part of measuring the level of competitiveness that have products in the medium term. The indicator pursues an illustrative parameter inherent trade dynamics of the Central American region. The results of the indicator, allowed the presence of significant trade flows, based on the production of fresh fruit, led to a 77.33% Costa Rica. The competitiveness of the banana category, props, greater commercial dynamism (36%) with Honduras. Conclusive horizon in defiance of existing opportunities, Nicaragua is positioned as an uncompetitive market, devoid of value added and annex to a short list of crops.
Keywords: Competitiveness; Productivity; Comparative Advantage; Positioning; Growth